Phytochemical constituency profiling and antimicrobial activity screening of seaweed extracts collected from the Bay of Bengal Sea coasts - Md. Abdus Shukur Imran; Farhana Rumzum Bhuiyan; Sheikh Rashel Ahmed; Parsha Shanzana; Mahmuda Akter Moli; Shakhawat Hossain Foysal; Suma Bala Dabi; Mahmudul Hasan (Journal of Advanced Biotechnology and Experimental Therapeutics, 2021)
Seaweeds are able to produce a great variety of secondary metabolites that are characterized by a broad spectrum of biological activities. Two seaweeds species, namely Hypnea musciformis and Enteromorpha intestinalis were studied to evaluate the phytochemical constituency and antimicrobial activities. First of all, crude extracts of both sea weeds were prepared by two different extraction methods (soaking and water bath) using different solvents. Phytochemicals profiling results revealed the presence of bioactive compounds (flavonoids, alkaloids, tannin, saponin and phenols) in both seaweed extracts. Quantification results for ethanolic extracts of H. musciformis and E. intestinalis estimated 51 mg and 43 mg tannins in per gram of dried samples and flavonoids contents were found 67 mg and 57 mg/g mg QE/g respectively. Total phenolic contents were determined in terms of gallic acid equivalent (GAE). H. musciformis exhibited higher amount of phenolics (59 ± 0.0002 mg GAE/g) than E. intestinalis extracts (41 ± 0.0002 mg GAE/g). In antimicrobial activity test, ethanol extracts of H. musciformis and E. intestinalis were found 10 mm of inhibition diameter against all of the bacterial strains. Besides, methanol extracts of E. intestinalis were more susceptible to Staphylococcus aureus and Pseudomonas which was close to the inhibition diameter (>15 mm) of the mainstream antibiotic; Gentamicin. Moreover, Klebsiella sp. was found more susceptible to ethanol and methanol extracts of Hypnea musciformis as it showed inhibition zone greater than 15 mm. Both Seaweed extracts possessed higher amount of phytochemicals and showed promising antimicrobial activities when compared with the standards. [ J Adv Biotechnol Exp Ther 2021; 4(1.000): 25-34]